Colorectal cancer in southern Israel: Comparison between Bedouin Arab and Jewish patients. (September 2016) - Smirnov, Michael; Lazarev, Irina; Perry, Zvi Howard; Ariad, Samuel; Kirshtein, Boris
Abstract: Purpose: Colorectal cancer (CRC) is the second most common malignancy and the third leading cause of cancer deaths in Israel; it is less common among the Arab than the Jewish population. This study compares the clinico-pathologic features, treatment, and prognosis between Bedouin-Arab (BA) and Jewish CRC patients treated at our medical centre. Methods: The medical records of 56 BA patients with CRC were compared retrospectively to 115 Jewish patients. Collected data included age, gender, history of smoking, family history of cancer, presenting symptoms, laboratory tests, previous malignancy, tumor characteristics, surgery type, stoma formation and closure, types of adjuvant treatment, and outcome. Results: BA patients were younger (mean age 68 versus 57 years, p  < 0.001), showed a higher incidence in females ( p  = 0.045), and had a lower frequency of a family history of cancer ( p  = 0.005) compared to Jewish patients. BA patients had a higher presentation of rectal bleeding and a lower rate of anemia at tumor diagnosis ( p  = 0.05 and p  = 0.004, respectively) with a more distal location of the tumor ( p  = 0.003). BA patients more often received chemotherapy and radiotherapy ( p  = 0.02 and p  = 0.04, respectively). Disease-free survival was shorter among BA patients ( p  = 0.023); overall survival was similar in both groups. Conclusions: CRC in BAs is characterized by a higher proportion of female, younger age, and higher proportion of distal location compared to Jewish patients. These differences in biology may be related to differences in past lifestyles and diet of BA compared to Jewish patients, and are expected to decrease in the following years as the BA population continues to undergo "westernization" changes. Highlights: This is a first comparison of CRC in different population in Southern Israel. Presenting sign of rectal bleeding is more frequent among Bedouin Arabs. CRC in Bedoun Arabs is characterized by a higher female rate, younger age, and higher rates of distal location compared to Jewish patients.